Callus Growth and Development of Cayenne Pepper (Capsicum frutescens L.) in Response to Glucose Concentration and Explant Source: Implications for Capsaicin Production via Tissue Culture - Syaiful Anam, Muhammad; Nurchayati, Yulita; Setiari, Nintya; Nuryandani, Einstivina (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2026)
Callus culture is a promising biotechnological approach for the sustainable production of secondary metabolites, including capsaicin, without dependence on seasonal factors or large-scale cultivation. This study investigated the effect of glucose concentration on callus growth derived from hypocotyl and cotyledon explants of Capsicum frutescens L. seedlings. A Completely Randomised Design with two factors and three replications was applied using Murashige and Skoog medium supplemented with 2 ppm 2,4-D and 0.5 ppm kinetin, and three glucose concentrations: 30, 40, and 50 g/L. Observed parameters included callus initiation time, colour, texture, and wet weight. Data were analysed using two-way ANOVA and Duncan's Multiple Range Test at P < 0.05. Glucose at 30 g/L produced the fastest initiation and highest wet weight in hypocotyl-derived callus, whereas 40 g/L was optimal for cotyledon-derived callus. These findings provide a basis for optimising tissue culture protocols to support capsaicin production in C. frutescens. Pertumbuhan dan Perkembangan Kalus Cabai Rawit (Capsicum frutescens L.) sebagai Respon terhadap Konsentrasi Glukosa dan Sumber Eksplan: Implikasinya terhadap Produksi Kapsaisin melalui Kultur Jaringan ABSTRAK: Kultur kalus merupakan pendekatan bioteknologi yang menjanjikan untuk produksi metabolit sekunder, termasuk kapsaisin, secara berkelanjutan tanpa bergantung pada faktor musiman maupun budidaya skala luas. Penelitian ini bertujuan mengkaji pengaruh konsentrasi glukosa terhadap pertumbuhan kalus yang berasal dari eksplan hipokotil dan kotiledon Capsicum frutescens L. Rancangan Acak Lengkap dengan dua faktor dan tiga ulangan digunakan pada media Murashige dan Skoog yang diperkaya 2 ppm 2,4-D dan 0,5 ppm kinetin, serta tiga konsentrasi glukosa, yaitu 30, 40, dan 50 g/L. Parameter yang diamati meliputi waktu inisiasi kalus, warna, tekstur, dan berat basah. Data dianalisis menggunakan ANOVA dua arah dan uji Duncan pada taraf P < 0,05. Glukosa 30 g/L menghasilkan inisiasi tercepat dan berat basah tertinggi pada kalus hipokotil, sedangkan 40 g/L optimal untuk kalus kotiledon. Temuan ini menjadi dasar optimasi kultur jaringan untuk mendukung produksi kapsaisin pada C. frutescens.